Bangladesh Shishu Academy : Dhaka-Sylhet Highway, Narsingdi - Kabir, Khandoker Upama (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2017.